Impact of catheter ablation of ventricular tachycardia in patients with prior myocardial infarctions. Issue 6 (20th April 2016) - Fukunaga, Masato; Goya, Masahiko; Hiroshima, Kenichi; Hayashi, Kentaro; Ohe, Masatsugu; Makihara, Yu; Nagashima, Michio; An, Yoshimori; Shirai, Shinichi; Ando, Kenji; Yokoi, Hiroyoshi; Iwabuchi, Masashi
Abstract: Background: Catheter ablation can reduce episodes of ventricular tachycardia (VT) after myocardial infarction (MI). However, the optimal endpoint of the ablation procedure remains unclear. Methods: Fifty‐one consecutive patients who received catheter ablation for VT after MI were included. The procedures targeted the isthmus of all the induced, sustained VTs. When the patients with induced VTs were hemodynamically stable, radiofrequency energy was delivered at the mid‐diastolic potential recording site during VT. When the patients with VTs were hemodynamically unstable, the critical channel was identified at the delayed potential recording site, showing a good pace map, with a long stimulus‐QRS interval. We delivered radiofrequency energy along the identified isthmus and across the exit of the circuit. Results: At the end of the procedure, all VTs became non‐inducible in 30 patients (59%) and some VTs were inducible in 21 patients (41%). During a mean of 40±29 months of follow‐up, no VT or ventricular fibrillation recurred in 24 patients (80%) in the non‐inducible group and in 12 patients (57%) in the inducible group, respectively ( P =0.03). The identification of the channel during VT mapping tended to associate with no recurrence, although the difference was not statistically significant ( P =0.2). Fourteen patients (27%) died during the follow‐up period, mostly due to non‐cardiac causes. Conclusions: The catheter ablation targeting the isthmus of prior‐MIVT and non‐inducibility at the end of the procedure can provide a satisfactory follow‐up result.